Aplicación móvil para sistematizar el proceso de pedidos en el restaurante de Comida Rápida Pollo Express - Cherrez Chinche, Washington Joan (2024)
The purpose of this degree project is to develop a mobile application aimed at managing the oversaturation and disorganization in the reception of orders by customers at the fast food restaurant "Pollo Express". To identify the problem, needs and complaints of customers, both interviews and surveys were used. In development, the "Mobile-D" methodology was chosen, which includes five phases: exploration, initiation, production, stabilization and system testing. By using this methodology, customer satisfaction was improved by taking into account their feedback, obtained through surveys and interviews. The architecture used to develop the application system was Mobile-D. As already indicated, this report is organized into the different chapters mentioned above. Keywords: Mobile – D, Delivery, Software, Systematize processes